Tawafuq (Miraculous Visual Alignments) In The Quran - Sabah Hussain (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Upon informing various Muslims (including Muslims living in Britain and the Middle East) about Tawafuq, I understood that many of them, including imams and various other professionals working with the Quran, seemed unaware of Tawafuq (miraculous alignment) in the Quran. How and why did so many Muslims seem unaware of one of the most important features of the Holy Quran? Tawafuq could save the faith of many, especially in an era where sight is often elevated in epistemology, many seem convinced only by what they can see, and where the sciences are often marked by an emphasis on empiricism. The article below seeks to introduce Tawafuq, and indicate its potential to be an important new field in Quranic studies.